Outcomes of pubertal development in girls as a function of pubertal onset age. Issue 5 (November 2018) - German, A; Shmoish, M; Belsky, J; Hochberg, Z
Abstract : Background: The relationship between pubertal onset and tempo and pubertal growth is controversial. We hypothesized that the age at onset of girls' puberty predicts pubertal tempo and the rate of pubertal progression. Methods: We analyzed the data of 380 girls from the prospective Study of Early Child Care and Youth Development (SECCYD) who were recruited in the USA from 1991 to 2006 and followed from birth to age 15.5 years. We used the following indicators: thelarche age (Tanner stage B2), pubarche age (P2), menarche age (M), the age when breast (B5) and pubic hair (P5) became fully mature, pubertal growth, pubertal duration (time from B2 to B5) and pubertal progression (time from B2 to M). We clustered the girls according to B2 age into early onset (EO; <9.4 years), intermediate (IO; 9.4–10.5 years), late onset (LO; >10.5 years). Results: All indicators of pubertal onset and conclusion occurred earlier in the EOs than in the LOs; yet, the differences in the age at main pubertal milestones lessened as puberty progressed: 2 years for B2; −1.4 years for M; −1 year for B5. In EOs, puberty was 1 year (average) longer than in LOs. Although EOs grew 7 cm (average) more than LOs, their heights at B5 were comparable. There was a significant relationship between the thelarche age and puberty tempo ( r = 0.23, P < 0.0001). Conclusions: The study highlights the predictive nature of variation in the onset age of puberty on its progression and duration. These results are reassuring in this context and will add to clinicians' and parental understanding of the expected milestones of puberty.